Currency Value Changes: Historical Dynamics and Islamic Legal Perspectives in Maqāṣid Ash-Shari’ah: Perubahan Nilai Mata Uang: Dinamika Sejarah dan Hukum Islam dalam Perspektif Maqāṣid Asy-Syari’ah - Darussalam, Ishlahu; Muhammad, Izbik (Az-Zarqa’: Jurnal Hukum Bisnis Islam, 2025)
Abstract: This article discusses the fluctuations in currency value throughout the history of Islamic economics, from the precious metal-based monetary system (gold and silver) to the use of paper money. This study also examines scholars’ views on the legal status of paper money and the challenges faced by the contemporary monetary system, such as inflation and usury (riba). The objective of this research is to explore the history of currency value fluctuations in Islamic economics, as well as how these developments have influenced the application of Islamic law in the history of economic transactions. The article also reviews various scholarly opinions regarding paper money, which are expected to provide a foundation for creating a more stable monetary system in line with Shariah principles. Based on these two aspects, the article seeks to analyze the challenges of the contemporary monetary system and reconstruct the theoretical foundations for a financial system that aligns with the principles of Maqāṣid Ash-Sharī’ah, such as protecting wealth (ḥifẓ al-māl), justice (al-‘adl), and the welfare of the community (maṣlaḥāt). This research employs a qualitative approach to analyze historical literature and Islamic law related to changes in the monetary system and the challenges posed by fiat currencies. The study finds that the transition from a metal-based monetary system (gold and silver) to paper money introduces challenges related to inflation and riba, which contradict the principles of Maqāṣid Ash-Sharī’ah. Therefore, the study emphasizes the need for a more stable monetary policy aligned with Shariah principles, with technology-based solutions such as asset-backed currencies or cryptocurrency as a more stable alternative free from exploitative debt practices classified as riba. Abstrak: Artikel ini membahas perubahan nilai mata uang dalam sejarah ekonomi umat Islam, mulai dari sistem moneter berbasis logam mulia (emas dan perak) hingga penggunaan mata uang kertas. Penelitian ini juga mengkaji pandangan para ulama mengenai status hukum mata uang kertas dan tantangan yang dihadapi oleh sistem moneter masa kini, seperti inflasi dan riba. Tujuan dari penelitian ini adalah untuk mengeksplorasi sejarah perubahan nilai mata uang dalam ekonomi Islam, serta bagaimana perkembangan ini mempengaruhi penerapan hukum Islam dalam sejarah transaksi ekonomi. Artikel ini juga meninjau berbagai pandangan ulama mengenai mata uang kertas, yang diharapkan dapat memberikan dasar bagi penciptaan sistem moneter yang lebih stabil dan sesuai dengan prinsip-prinsip syariah. Dari dua hal tersebut, artikel ini mencoba untuk membaca tantangan sistem moneter di era kontemporer dan menyusun kembali dasar teotertik untuk sistem keuangan yang sesuai dengan prinsip-prinsip dalam Maqāṣid Asy-Syarī’ah seperti menjaga harta (hifẓ al-māl), keadilan (al-‘adl), dan kepentingan kesejahteraan umat (maṣlaḥāt). Penelitian ini menggunakan pendekatan kualitatif untuk menganalisis literatur sejarah dan hukum Islam mengenai perubahan sistem moneter dan tantangan mata uang fiat. Penelitian ini menemukan bahwa perubahan dari sistem moneter berbasis logam (emas dan perak) ke uang kertas memunculkan tantangan terkait inflasi dan riba, yang bertentangan dengan prinsip Maqāṣid Asy-Syarī’ah. Oleh karena itu, penelitian ini menekankan perlunya kebijakan moneter yang lebih stabil dan sesuai dengan prinsip-prinsip syariah, dengan solusi berbasis teknologi seperti mata uang yang didukung aset atau cryptocurrency sebagai alternatif yang lebih stabil dan bebas dari praktik utang eksploitatif yang tergolong riba.